GOODS DELIVERY SYSTEM DESIGN IN PT. POS INDONESIA MAMPANG PRAPATAN USING VISUAL BASIC 6.0 - Eris Kurniawan; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2001)
In this writing, the author tries to help facilitate PT. Pos Indonesia Mampang Prapatan inaddressing problems arising from the errors that often occur in the process of makingdelivery of goods by way of report design systems based on the information producedwhat is expected, so it can avoid wasting time and remaining time can be used for otheruseful activities.Storage of document delivery as an archive of stacked paper can be replaced by using themedia Hard Disk as a place to store files that are used in the delivery of the goods. Byusing the file does not require large space and data access becomes faster and moreefficient.Reports generated by the proposed delivery system is more complete and does not requiretoo much time to make a report. Employees can print the desired report by simplyselecting a menu that is available, so that the control of management to be better in orderto improve delivery productivity.